Optimalisasi Prestasi Belajar Ilmu Pengetahuan Sosial Melalui Media Visual di SMP - Kris Suwarti (Manajemen Pendidikan, 2016)
This  research  aim  to description  of optimalisation  of achievement  of learning through visual medium at educative  participant  of class IX E State Junior High School Two Cawas Region Klaten school year odd semester 2014/2015. Subject and research data source is educative participant  of class VIII F 21 educative participants.  Data collecting method  applies  observation,   documentation,   and  test.  Data  analysis  applies  critical analysis  and  comparability.  Indicator  success  of  using  minimal  limit  criteria  75  and complete target of 100%. Research procedure applies cycle. Based on result of inferential research  and  solution  that  :  Data  obtained  from  finite  precycle  of  cycle  II,  obtained progress of achievement of student learning in study of Social science with materi environmental  development passed visual picture/ medium, at precycle average of 71,6 and cycle I average of 76,6 and cycle II average of 84,9. From this data, seems to explain that happened increase of average of value from precycle to cycle I equal to 5 number (7%), from cycle  I  to  cycle  II  happened  increase  8,3  numbers  (10,8%),  from  pasiklus  to  cycle  II happened increase 13,3 numbers (18,6%).Highest  value of phase precycle 80 and cycle I 86 and cycle II 92. Seems to explain that from phase precycle to cycle I happened increase equal to 6 number (7,5%), from cycle I to cycle II happened increase equal to 6 number (7%), and from precycle to cycle II happened increase 10 numbers (13%). Low value of phase precycle is obtained by 66 and cycle I 72 and cycle II 76. thereby, can be affirmed that from phase precycle  to cycle  I happened  increase  equal  to 6 number  (9%),  from  cycle  I to cycle  II happened  increase  equal  to  4  number  (5,6%),  and  from  precycle  to  cycle  II  happened increase  10 numbers (15,2%).Complete  percentage  learnt starts from precycle  is obtained equal to 24% and cycle I is obtained  equal to 62% and cycle II equal to 100%. Seems to explain that from phase precycle to cycle I happened increase equal to 38%, from cycle I to cycle II happened  increase equal to 38%, and from precycle  to cycle II happened  increase equal to 76%.  Thereby,  achievement  of student  learning  in study  of Social  science  with materi environmental  development  passed visual picture/  medium  from finite precycle  of cycle II happened increase significant.